Hubungan Manajemen Perawatan Diri dengan Kualitas Hidup pada Pasien Hipertensi di Puskesmas Tuminting Manado - Manansang, Novan Kristorio; Pondaag, Ferlan Ansye; Toar, Juwita Moreen (Mapalus Nursing Science Journal, 2025)
Abstract Background: Hypertension is a chronic disease that significantly contributes to global morbidity and mortality. Optimal hypertension management requires active patient involvement through self-care management, which is believed to contribute to improved quality of life. Objective: To determine the relationship between self-care management and the quality of life of hypertensive patients at the Tuminting Public Health Center in Manado. Methods: A total of 74 respondents were selected using purposive sampling. The instruments used included the Hypertension Self-Management Behavior Questionnaire (HSMBQ) to assess self-care management and the World Health Organization Quality of Life (WHOQOL-BREF) questionnaire to assess quality of life. Data were analyzed using univariate analysis for frequency distribution and bivariate analysis with Spearman’s correlation test. Results: The majority of respondents (83.8%) had a moderate level of self-care management, and 81.1% had a poor quality of life. Bivariate analysis showed a significant relationship between self-care management and quality of life (p = 0.000; r = 0.402). Conclusion: There is a significant relationship between self-care management and quality of life among hypertensive patients at the Tuminting Public Health Center in Manado. These findings highlight the importance of enhancing self-care education through practical programs at primary healthcare centers, such as self-monitoring training, healthy lifestyle counseling, as well as involving family support and utilizing simple technologies to improve adherence and quality of life in patients with chronic diseases. Keywords: chronic disease; Hypertension; quality of life; self-care management